Distribute
(3/4)(4c)+(3/4)(16)=2c/9
3c+12=2/9 c
Now subtract 2/9 c from both sides
3c+12-2/9 c=2/9 c-2/9 c
25/9 c+12 =0
Now we need to subtract 12 from both sides
25/9 c+12-12=0-12
25/9 c=-12
Just multiply both sides by 9/25 so we find the value for c
25/9 *(25/9 c)=-12(9/25)
c= -108/25
I hope that's help:0
A - C is less than or equal to 26.
B - C is less than or equal to 78.
C - C is greater than or equal to 26.
D - C is greater than or equal to 52.
4x + 3y + z= -6
x-3y + 2z=0
11x-2y + 3z = - 26
Answer:
y= - 271/71
x=755/71
z =4866/71
Step-by-step explanation:
For resolve a system you multiply an equation of the system or add two of the equation and replace the result in the system
Add the 1st and 2nd, and replace the 2nd
4x + 3y + z= -6 4x + 3y + z= -6 4x + 3y + z= -6
(-4) (x-3y + 2z=0) → -4x +12y -8z =0 → +15y -7z = -6
11x-2y + 3z = - 26 11x-2y + 3z = - 26 11x-2y + 3z = - 26
Add the 2nd and 1st, and replace the 1st
4x + 3y + z= -6 4x + 3y + z= -6 4x + z= -6
(-1/5)( 15y -7z = -6) → -3y -7/5z =6/5 → -3y -7/5z =6/5
11x-2y + 3z = - 26 11x-2y + 3z = - 26 11x-2y + 3z = - 26
Add the1st and 3rd, and replace the 3erd
(-3)( 4x + z= -6) -12x - 3z= 18 -12x - 3z= 18
-3y -7/5z =6/5 → -3y -7/5z =6/5 → -3y -7/5z =6/5
11x-2y + 3z = - 26 11x-2y + 3z = - 26 -x-2y = - 8
Add the1st and 3rd, and replace the 1st
(1/3)(-12x - 3z= 18 ) -4x - z= 6 -4x - z= 6
(5)(-3y -7/5z =6/5) → -15y - 7z = 6 → -15y - 7z = 6
-x-2y = - 8 (-4)(-x-2y = - 8) 4x + 8y= 32
Add the 1st and 2nd, and replace the 2nd
(-7)(8y - z =38) -56y +7z= 266 -56y +7z= 266
-15y - 7z = 6 → -15y - 7z = 6 → -71y=271 → y= - 271/71
(1/4)(4x + 8y= 12) x+2y=3 x+2y=3
-56y +7z= 266 → -8y + z =38 → z =4866/71
x+2y=3 → x=755/71